Analysis of rain and reservoir water using ICP-OES and IC. - Toh, Boon Teck. (2010)
A study of the chemical composition of rainwater and 3 reservoirs in Singapore, Upper Seletar Reservoir, Kranji Reservoir and Jurong Lake Reservoir, was carried out for 3 months from January 2010 to March 2010. Samples were analyzed using ICP-OES and IC. Reservoir water was alkaline and rainwater was acidic with 75% of sample below pH 4.8. Pearson’s correlation and Principal Component Analysis was done for the Reservoirs and rainwater samples. It was theorized that the main factors influencing the water quality were sea salt, crustal elements, combustion of fuel oil in power stations and traffic emission.